Sistem Pembayaran Zakat Via Online Perspektif Hukum Islam (Studi Kasus Badan Amil Zakat Nasional (Baznas) Kota Makassar) - Fadilah, Muhaimin Nur; Baedah, Said Syarifuddin Abu; A, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore in depth how the online zakat payment system is implemented by the National Zakat Agency (BAZNAS) of Makassar City and to analyze the Islamic legal perspective regarding the legality and validity of this system. The study employs a qualitative approach using a descriptive-analytical method. Data were collected through in-depth interviews with BAZNAS Makassar officials, direct observation of the online zakat payment system, and documentation from relevant sources.The findings reveal that the online zakat payment system at BAZNAS Makassar facilitates muzakki (zakat payers) in fulfilling their zakat obligations through digital channels such as the official website, QRIS, and virtual accounts. This system enhances efficiency, transparency, and accountability, although it still faces challenges such as low digital literacy, data security risks, and lack of public outreach. From an Islamic legal perspective, online zakat payments are considered valid as long as they fulfill the pillars and conditions of zakat and are managed by trustworthy amil (zakat administrators). Therefore, this system represents a technological innovation that aligns with contemporary needs without compromising the core principles of Islamic law.